Simultaneous Determination of 18 Effective Components in Chemical Medicines for Cold With HPLC-MS/MS - Zhang, Xi-Ru; Zhang, Yi-Hua; Jiang, Jian-Guo; Song, Geng-Shen; Zi, Yang (Asian Journal of Chemistry, 2012)
To establish a HPLC-MS/MS method for simultaneous determination of 18 effective components in chemical medicines for cold. The samples were extracted by methanol and were separated in an Altantis T3 column within 15 min with a gradient elution of acetonitrile- ammonium acetate (include 0.25 % glacial acetic acid), a tandem quadrupole mass spectrometer equipped with electrospray ionization source (ESI) was used in cationic, negative ion mode, multiple reaction monitoring was performed to quantify these compounds. Eighteen linear calibration curves were obtained, r = 0.9991. The precision of the method were good, RSD (n = 6) ranged from 0.23 % to 0.96 %. The method is simple, accurate and good reproducible for simultaneous determination multiple index components under the same chromatographic condition. It could be used to provide a reference for quality evaluation of chemical medicine for cold and monitor illegally added in traditional Chinese medicine for cold.